(3eaGgje ChdjI aj JMdjd GdSjGSI GdNGQLjI s - (3ejdhO(B, (3hdO GdUOjbs ((3YeGf (B:s (3eQcR GdcJGH GdCcGOjej(B,s, 2017)
(3eaghe h NUGFU h GgOGa GdSjGSI GdNGQLjI h YdGbJgG HGdeaGgje GdeTGHgI dgG h GdYhGed GdOGNdjI h GdNGQLjI GdeDKQI aj GdSjGSI GdNGQLjI h CKQ YGed GdbjGOI (B( (3UGfY GdbQGQ(B) (3aj JhLjg GdSdhc GdSjGSj eY JfGhd GdfXQjI GdhGbYjI h GddjHjQGdjI h GdHfGFjI GdeaSQI ddSjGSI GdNGQLjI h cPG eaghe h fXQjI h eOGNd h eQGMd GJNGP GdbQGQ h GdeOGNd GdfXQjI dOQGSI UfY GdbQGQ h eQGMd gPg GdYedjI h cPG GdJWQb Gdi eaghe YedjI GJNGP GdbQGQ aj GdSjGSI GdNGQLjI h GdCReI GdOhdjI h UfGYI GdbQGQ GdNGQLj h feGOL UfGYI GdbQGQ aj GdSjGSI GdNGQLjI h CNjQG GdgjFGJ GdeTGQcI aj UfGYI GdSjGSI GdNGQLjI HJfGhd GdeDSSGJ GdMchejI (B.s
(3eQGLY U(B.168 (3edGLb U(B.175s
Keywords: (3GdSjGSI GdNGQLjIs